Using of some phenotypes of Prunusursina K.Y in Lattakia as rootstock of Black amber - صبوح صفاء (Latakia University Journal -Biological Sciences Series, 2020)
This study was carried out during 2016 to determind the initial compatibility between PrunusursinaKY and Diamond plum (Black amber) by using tongue grafting. (18) trees of PrunusursinaKy genotypes prevailing in 3 sites of Lattakia (Dwerbsndiana, Alnabeen, Btmaza) was selected for the analysis. Grafting performed during the first week of February. Percentage of grafting succesfulsurvival got to 83،78،100))% respectively in (Dwerbsndiana, Alnabeen, Btmaza)withoutsignificant difference. Types prevailing in Alnabeen were more significant than those of Dwerbsndianain terms of number of branches.There was no significant difference in terms oflongitudegrowths after two monthes of grating, at end of August,and latitude growths after two monthes, while Btmaza wasmore significant thanAlnabeenin both, terms of latitude growths after two monthes, and measure of longitude and latitude growths.